2013 IEEE Conference on Computer Vision and Pattern Recognition 2013
DOI: 10.1109/cvpr.2013.191
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Modeling and Relighting of Reflective-Fluorescent Scenes

Abstract: Hyperspectral reflectance data allows for highly accurate spectral relighting under arbitrary illumination, which is invaluable to applications ranging from archiving cultural e-heritage to consumer product design. Past methods for capturing the spectral reflectance of scenes has proven successful in relighting but they all share a common assumption. All the methods do not consider the effects of fluorescence despite fluorescence being found in many everyday objects. In this paper, we describe the very differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Previous work has also shown that absorption spectra can be well represented by basis functions [10]. In our investigation, we have found that a large collection of absorption spectra from the McNamara and Boswell Fluorescence Spectral Dataset [13] can be well represented using 9 principal components.…”
Section: Fluorescence Absorption Spectrum Recoverymentioning
confidence: 89%
See 3 more Smart Citations
“…Previous work has also shown that absorption spectra can be well represented by basis functions [10]. In our investigation, we have found that a large collection of absorption spectra from the McNamara and Boswell Fluorescence Spectral Dataset [13] can be well represented using 9 principal components.…”
Section: Fluorescence Absorption Spectrum Recoverymentioning
confidence: 89%
“…In recent work, methods for hyperspectral imaging of reflective-fluorescent scenes have been proposed. Lam and Sato [10] provided a method for recovering the full spectral reflectance and fluorescence absorption and emission spectra of scenes but they require a multiband camera and multiple narrowband illuminants. Fu et al [4] also recovered the full spectral reflectance and fluorescence spectra of scenes by using high frequency light spectra but they require a hyperspectral camera and a programmable light source: a device that can be programmed to produce arbitrary light spectra.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because fluorescence can provide additional information about scenes and has been applied to problems in camera spectral sensitivity estimation [1], 3D reconstruction [2], [3], immersion range scanning [4], and color relighting [5], [6] to name a few.…”
Section: Introductionmentioning
confidence: 99%